Dual axis tracking model for a heliostat field solar tower heat flux investigation - Ali, B.H. (Asian Research Publishing Network, 2016)
The heat flux density and distribution are the main dominant design parameters for the solar tower plant output power and receiver formation. Beside the plant geometries of the tower height, heliostat dimensions, field layout, and the optical properties, the quality of these two values depends on the heliostat field efficiency, which outlined in the mirror tilt angle cosine effect, reflected rays' spillage loss, heliostat distribution blocking and shadowing and tracking control error. To investigate the annual heat flux collecting quantity and distribution for an experimental field, distributed and located in Universiti Teknologi Petronas, a detailed dual axis tracking model is elaborated herein. Â© 2006-2016 Asian Research Publishing Network (ARPN).